Pengukuran Literasi Zakat di Kecamatan Lima Kaum Kabupaten Tanah Datar - Laily Hidayati; Syukri Iska (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Andalas, 2023)
This study aims to measure Zakat Literacy Index of a Muslim community using a measurement technique developed by the Indonesian National Zakat Board. This was a cross-sectional study at Sub District Lima Kaum, Tanah Datar – West Sumatera Province. This research used survey questionnaires to collect data involving 200 respondents (93 muzakki who paid zakat directly to recipients and 107 muzakki who paid zakat through institutions). The results showed that the Zakat Literacy Index at Sub-District Lima Kaum was categorized as „low‟ (score = 42.19). Score achieved for basic knowledge of zakat was 31.57 whereas for advanced knowledge was much lower (10.63). This result can be an input for stakeholders on how to improve zakat literacy of the Muslim community.